Impairment of paravascular clearance pathways in the aging brain. Issue 6 (26th September 2014) - Kress, Benjamin T.; Iliff, Jeffrey J.; Xia, Maosheng; Wang, Minghuan; Wei, Helen S.; Zeppenfeld, Douglas; Xie, Lulu; Kang, Hongyi; Xu, Qiwu; Liew, Jason A.; Plog, Benjamin A.; Ding, Fengfei; et al.
<x xml:space="preserve">Abstract</x> Objective In the brain, protein waste removal is partly performed by paravascular pathways that facilitate convective exchange of water and soluble contents between cerebrospinal fluid (CSF) and interstitial fluid (ISF). Several lines of evidence suggest that bulk flow drainage via the glymphatic system is driven by cerebrovascular pulsation, and is dependent on astroglial water channels that line paravascular CSF pathways. The objective of this study was to evaluate whether the efficiency of CSF–ISF exchange and interstitial solute clearance is impaired in the aging brain. Methods CSF–ISF exchange was evaluated by in vivo and ex vivo fluorescence microscopy and interstitial solute clearance was evaluated by radiotracer clearance assays in young (2–3 months), middle‐aged (10–12 months), and old (18–20 months) wild‐type mice. The relationship between age‐related changes in the expression of the astrocytic water channel aquaporin‐4 (AQP4) and changes in glymphatic pathway function was evaluated by immunofluorescence. Results Advancing age was associated with a dramatic decline in the efficiency of exchange between the subarachnoid CSF and the brain parenchyma. Relative to the young, clearance of intraparenchymally injected amyloid‐β was impaired by 40% in the old mice. A 27% reduction in the vessel wall pulsatility of intracortical arterioles and widespread loss of perivascular AQP4 polarization along the penetrating arteries accompanied the decline in CSF–ISF exchange. Interpretation We propose that impaired glymphatic clearance contributes to cognitive decline among the elderly and may represent a novel therapeutic target for the treatment of neurodegenerative diseases associated with accumulation of misfolded protein aggregates. Ann Neurol 2014;76:845–861